Origin, diversification and substrate specificity in the family of NCS1/FUR transporters. - Krypotou, Emilia; Evangelidis, Thomas; Bobonis, Jacob; Pittis, Alexandros A; Gabaldón, Toni; Claudio Scazzocchio; Mikros, Emmanuel; Diallinas, George (Mol Microbiol, 2015)
NCS1 proteins are H(+) /Na(+) symporters specific for the uptake of purines, pyrimidines and related metabolites. In this article we study the origin, diversification and substrate specificity of fungal NCS1 transporters. We show that the two fungal NCS1 subfamilies, Fur and Fcy, and plant homologues, originate through independent horizontal transfers from prokaryotes, and that expansion by gene duplication led to the functional diversification of fungal NCS1. We characterized all Fur proteins of the model fungus Aspergillus nidulans and discovered novel functions and specificities. Homology modelling, substrate docking, molecular dynamics and systematic mutational analysis in three Fur transporters with distinct specificities identified residues critical for function and specificity, located within a major substrate binding site, in transmembrane segments TMS1, TMS3, TMS6 and TMS8. Most importantly, we predict and confirm that residues determining substrate specificity are located not only in the major substrate binding site, but also in a putative outward-facing selective gate. Our evolutionary and structure-function analysis contributes in the understanding of the molecular mechanisms underlying the functional diversification of eukaryotic NCS1 transporters, and in particular, forward the concept that selective channel-like gates might contribute to substrate specificity.